002.1 Point-of-care testing and immediate treatment of curable sexually transmitted and genital infections among antenatal women in papua new guinea. (13th September 2015) - Badman, SG; Vallely, LM; Toliman, P; Kariwiga, G; Tabrizi, S; Pomat, W; Guy, R; Homer, C; Luchters, S; Morgan, C; Garland, SM; Rogerson, S; et al.
Abstract : Background: Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Trichomonas vaginalis (TV) and bacterial vaginosis (BV), are associated with adverse maternal and neonatal health outcomes, particularly preterm birth and low birth weight. These infections are highly prevalent in many low-income settings but remain undiagnosed and therefore untreated in pregnancy because of a lack of suitable diagnostic technology. In 2014, we conducted the first feasibility study of newly-available, easy to use and highly-accurate point-of-care (POC) STI assays in a routine clinical setting in Papua New Guinea (PNG) in preparation for a large-scale field trial to evaluate the potential of this strategy to improve pregnancy outcomes. Methods: Women aged 18–35 years attending their first antenatal visit were invited to participate. Following informed consent procedures, women completed a short interview, obstetric examination, and provided self-collected vaginal specimens for clinic-based STI testing, conducted by trained clinic staff: CT/NG and TV were tested using the Cepheid GeneXpert platform, and BV tested using the BVBlue Test. Participants were provided with same-day POC test results, and antibiotic treatment as indicated. Women were also provided routine onsite antenatal HIV and syphilis screening. Results: A total of 125 women were enrolled. The prevalence of CT was 20.0%; NG, 11.2%; TV, 37.6%; BV 18.4%; and more than half (67/125) had one or more of these infections. Over 70% of those with a POC-confirmed STI would not have been detected on clinical grounds alone. The prevalence of HIV was 1.6% and active syphilis, 4.0% in this population. All women with an STI and their sexual partners were successfully treated. Conclusion: Antenatal POC STI testing and treatment proved feasible in an antenatal setting in PNG. If this strategy is proven to be effective in our future field trial (2015–18), it has the potential to improve pregnancy outcomes in all high-burden, low-income countries worldwide. Disclosure of interest statement: Nothing to Disclose